Pengaruh Model Pembelajaran Induktif Terhadap Kemampuan Berpikir Kritis - Ramadhan, Avinda Zakcy; Arianto, Fajar; Kristanto, Andi (LP. Ma'arif Janggan Magetan, 2024)
This study aims to test the influence of the inductive learning model on the critical thinking ability of grade IX students in science subjects in junior high school. A quantitative approach with a quasi-experimental method is used in this study. The research subjects consisted of students of class IX A as the experimental group and class IX B as the control group. The research instruments included questionnaires and tests to measure critical thinking skills before and after treatment. The results of data analysis showed that the inductive learning model had a positive and significant effect on students' critical thinking skills. In conclusion, the application of the inductive learning model can improve critical thinking skills in science learning.